The development of a soft skill questionnaire for compulsory university courses based on blended learning - Ponmalar, Ponmalar N.; Yee, Wendy Mei Tien; Che Husain, Faridah; Mat Noor, Noor Ain (2018)
This study focuses on enrichment of soft skills elements embedded in a compulsory university course, namely, the Ethnic Relations through blended learning. A questionnaire was developed to measure the embedded soft skills elements i.e. teamwork, communication skills and problem-solving & critical thinking. A pilot study was done to test the reliability and validity of the instrument amongst first year students enrolled in the Ethnic Relations course. It also aims to measure the early stage of soft skills embedment amongst students. The questionnaire contains 5 parts, part A consist of demography information, part B on communication skills, part C on critical thinking & problem solving, part D team work skills and Part E – an open ended question on the respondents experiences and reflection. A total of 232 completed questionnaire were analysed using Statistical Package for Social Science (SPSS) version 22 and structure equation modelling (SEM). The findings of the study showed that the validity and reliability of the questionnaire was suitable in measuring the level of soft skills amongst the students.